POLA PEMANFAATAN RUANG VERTIKAL DAN JELAJAH HARIAN ORANGUTAN SUMATERA (Pongo abelii, LESSON 1827) DI BLOK BARAT HUTAN BATANG TORU, SUMATERA UTARA) - Muhammad Faesal Rahman Hakim; Ani Mardiastuti; Entang Iskandar (Media Konservasi, 2015)
The most southern Sumatran orangutan natural habitat is located in Batang Toru Forest Block. This study aims to determine  use of vertical space and the daily range of Sumatran orangutans in Batang Toru Forest. At least 17 different individual have been identified, but only 7 individual have been habituated. This study aims to determine use of vertical space and the daily range of Sumatran orangutans in Batang Toru Forest, begun by examining 7 habituated individu. Data vertical space was collected by focal animal sampling and ad libitum by following the individual orangutan from nest in the morning until next nest in the dusk , with each 2 minute recording intervals. Orangutans used the vertical level on 16-25 m where the fruits were abundant or at the position 72,00-82,14% from the groumd. The mean day range is 760,73-1089,28 m. There is not difference between daily range of the orangutan adult male, adult female and adolescent ( F = 0.119 ; p value = 0.94 ; α = 0.05). Keywords: daily range, Sumatran orangutan, vertical space